A high-performance polycyanurate network derived from 4, 4′-biscyanato-2, 2′-trifluoromethylbiphenyl. Issue 4 (10th January 2020) - Liu, Jingfeng; Meng, Qingjie; Li, Liying; Lu, Gewu; Yuan, Hang; Cui, Lei; Liu, Xia; Mu, Hongliang; Ji, Jingjing; Zhou, Defeng; Wang, Zhen; Yan, Jingling
Abstract : Polycyanurates with excellent thermal, mechanical, and dielectric properties were derived from 4, 4′-biscyanato-2, 2′-trifluoromethylbiphenyl, and their properties were systematically compared with those of polycyanurates derived from bisphenol A dicyanate. Abstract : A novel dicyanate, 4, 4′-biscyanato-2, 2′-trifluoromethylbiphenyl (TFMBDCy), and its thermoset were prepared, and their properties were systematically compared to those of polycyanurates derived from bisphenol A dicyanate (BADCy). The TFMBDCy network exhibited a much higher glass transition temperature, enhanced toughness, reduced water uptake, and improved dielectric properties compared to the BADCy-derived polycyanurate. These improvements resulted from the fluorinated, rigid but non-coplanar architecture of TFMBDCy.